Answer:
Here is the answer.
Step-by-step explanation:
b) students are the frequency. so we need to add all the frequency.
5 + 4 + 7 + 10 + 4=30 students
c) here we need to use the summation.
total/ frequency= mean
6*5=30
7*4=28
8*7=56
9*10=90
10*4=40
we need to add them all= 244
total frequency= 30
mean = 244/30= 8.133333333...≈ 8 (this is a rounded of value as in 0.13, 3 goes on repeating.
Eruptions of the Old Faithful geyser have duration times with a mean of 245.0 sec and a standard deviation of 36.4 sec (based on sample data). One eruption had a duration time of 110 sec.
Answer:
Difference between time = -135 sec
Step-by-step explanation:
Given:
Mean eruption = 245 sec
Standard deviation = 36.4 sec
One eruption had a duration time of 110 sec
Find:
Difference between duration time of 110 sec and mean = ?
Computation:
⇒ Difference between time = One eruption duration time - Mean
⇒ Difference between time = 110 sec - 245 sec
⇒ Difference between time = -135 sec
Please help!!!!!!!!!!!!!!!
Answer:
C
Step-by-step explanation:
[tex]12x\sqrt{900x^2y^4z^6}= \\\\12x\sqrt{30^2x^2(y^2)^2(z^3)^2}= \\\\12x(30xy^2z^3)= \\\\360x^2y^2z^3[/tex]
Therefore, the correct answer is choice C. Hope this helps!!
hey mate iam indian
claim 10 points
Answer:
k
Step-by-step explanation:
solve each equation by graphing (work shown appreciated)
Answer:
Option A
Step-by-step explanation:
I used a graphing tool to graph the equations given. When graphed, the lines intercept at (-2,3). Therefore, it is the solution to the system of equations. See the picture attached for the graph.
Option A should be the correct answer.
Anyone know this ???
Answer:
A because it is super close together
Step-by-step explanation:
Answer:
B. 45°
Step-by-step explanation:
The angles of a triangle have to add up to 180°.
In this triangle C is given as 90°. That leaves 90° for the sum of the two others. Since the triangle is symmetrical, you can divide 90° by 2 to get to equal angles of 45°.
12.48 ÷ 7.6
[tex]12.48 \div 7.6 [/tex]
Answer:
2.08
Step-by-step explanation:
12.48 ÷ 6
= 2.08
Answer:
Hi
Answer:
= 1.6
Olivia is working two summer jobs, making $7 per hour walking dogs and making $15 per hour tutoring. In a given week, she can work a maximum of 18 total hours and must earn no less than $180. If x represents the number of hours walking dogs and y represents the number of hours tutoring, write and solve a system of inequalities graphically and determine one possible solution.
Answer:
x= 11.25 y=6.75
Step-by-step explanation:
we will present all of that to equations so we have
7x+15y=180
and x+y=18
by solving those 2 equations together we get the solution
how do i write 7 degrees warmer today than yesterdays temperature t
a square scarf has a side length of 3/4 yard on each side what is the area of the scarf??
Answer:
3 unit
Step-by-step explanation:
3/4 x 4 = 12/4 = 3
Answer:
its 3-
Step-by-step explanation:
but i need it in fraction--
I NEED HELP ASAP
A restaurant used 1⁄3 of a bag of spinach to make 2 servings of salad. How many bags of spinach did the restaurant put in each serving?
Answer:
1/6
Step-by-step explanation:
1/6
William just purchased a residential investment property for $225,000. William is 60, married, and will not occupy the property. Will this new property qualify for a homestead exemption?
Here is a sequence of patterns made from dots.
Find an expression, in terms of n, for the number of dots in Pattern number n.
Answer:
Hello
I think this is the answer: 3n+ n or 4n
And for fourth is 16 and fifth is 20
Step-by-step explanation:
can someone plzz help
Answer:
it's 12 because
2×6=12
3×4=12
4×3=12
and all of them have twelve
Answer:
it's 12 becauseStep-by-step explanation:
2×6=12
3×4=12
4×3=12
all of and them have twelve
Are the expressions –0.5(3x + 5) and –1.5x + 2.5 equivalent? Explain why or why not.
Answer:
No.
Step-by-step explanation:
If you distribute the 1st equation out, you will be able to see that it is -1.5x - 2.5 while the other equation is -1.5x + 2.5. Since you have to distribute the negative, they are not equivalent.
Answer:
Both expressions are not equal.
Step-by-step explanation:
-0.5(3x+5) = -1.5x - 2.5
–1.5x+2.5 = -1.5x + 2.5
The first expression results in subtracting 2.5, the second expression results in adding 2.5.
What is the measure of ZJKL?
(Not drawn to scale)
1370
Marke this and return
Answer:
JKL = 117
Step-by-step explanation:
63 and JKL form a straight line and their sum is 180
63+ KJL = 180
Subtract 63 from each side
63+ KJL - 63 = 180-63
JKL = 117
this is actually a question but shhhhh, just copy it and youll get points....Drag each description to the correct location on the table. Each description can be used more than once.
Classify each polynomial based on its degree and number of terms.
cubiccubicquarticquarticquinticquinticquadraticquadraticlinearlinearmonomialmonomialmonomialbinomialbinomialbinomialtrinomialtrinomial
The answer is what you got
cubiccubicquarticquarticquinticquinticquadraticquadraticlinearlinearmonomialmonomialmonomialbinomialbinomialbinomialtrinomialtrinomial
What is the value of n ?
Answer:
Your answer would be the letter a
Answer:
Step-by-step explanation:
180 -133 = 47
180-142=38
38+47= 85
180 - 85 = 95
180 - 95= 85
The answer is A
The speed of light is 3 x 108 m/s. If its frequency is 4.11 x 104 Hz, what is its wavelength?
The wavelength of the light wave is approximately 729.94 meters.
What is the speed of light?The speed of light is regarded as a fundamental natural constant. Its relevance extends well beyond its role in characterizing an electromagnetic wave characteristic.
The speed of light is a constant, and it is equal to the product of the frequency of a light wave and its wavelength.
The speed of light is 3 x 108 m/s. If its frequency is 4.11 x 104 Hz
So if the frequency of a light wave is given, we can use this formula to calculate its wavelength:
wavelength = speed of light / frequency
Plugging in the values given in the question, we get:
wavelength = 3 x 10⁸ m/s / 4.11 x 10⁴ Hz
wavelength = 3 x 10⁸/ 4.11 x 10⁴
wavelength = 3 / 4.11 x 10⁸/10⁴
Performing the calculation, we find that the wavelength of the light wave is approximately 729.94 meters.
To learn more about the speed of light click here:
https://brainly.com/question/394103
#SPJ5
The concession stand at the high school football stadium sells hot dogs and sodas. Jack bought 3 hotdogs and 2 sodas for a total of $12. Angie bought 1 hotdog and 4 sodas for $9. Solve a system of equations to determine the cost of 1 hotdog and 1 soda.
Answer: each soda costs $1.5 and each hotdog costs $3.
Step-by-step explanation:
If H is the price for one hotdog and S is the price for one soda, we have the equations:
for Jack.
3*H + 2*S = $12
For Angie.
1*H + 4*S = $9
Now we can isolate one of the variables in one of the equations and then replace it in the other equation, let's isolate H in the second equation:
H = $9 - 4*S
now we replace it in the first eq
3*H + 2*S = $12
3*($9 - 4*S) + 2*S = $12
$27 - 12*S + 2*S = $12
-10*S = $12 - $27 = -$15
S = $15/10 = $1.5
Now we can replace it in the equation for H and get:
H = $9 - 4*$1.5 = $3
So each soda costs $1.5 and each hotdog costs $3.
Answer: One hotdog cost $3 and One soda costs $1.5
Step-by-step explanation:
Let hotdogs be denoted by h
Let sodas be denoted as s
Jack bought 3 hotdogs and 2 sodas for a total of $12. This can be written as:
3h + 2s = 12
Angie bought 1 hotdog and 4 sodas for $9. This can be written as:
h + 4s = 9
3h + 2s = 12
h + 4s = 9
1 × (3h + 2s = 12)
3 × (h + 4s = 9)
3h + 2s = 12
3h + 12s = 27
Subtract the equation
-10s = -15
s = -15/-10
s = 1.5
One soda cost $1.5
Since h + 4s = 9
h + 4(1.5) = 9
h = 9 - 6
h = 3
One hotdog costs $3
g(x) = -3x – 8
g()=10
Answer:
g(-6) = 10
Step-by-step explanation:
-3x - 8 = 10
-3x = 18
x = -6
If the cost price of 10 chairs equal to the selling price of 16 chairs. Find the profit or loss percent please.
Answer:
The answer should be 37.5%
Step-by-step explanation:
Find the zeroes of the quadratic polynomial 4√3x2+5x -2√3
The volume of a sphere whose diameter is 18 centimeters is _π cubic centimeters
Answer:
12 pi cubic cm
Step-by-step explanation:
Please help! Correct answer only, please! I need to finish this assignment this week. Determine the value of the following: A. B. C. D.
Answer:
B
Step-by-step explanation:
Given
[tex]\left[\begin{array}{ccc}3&2\\-4&6\\7&5\end{array}\right][/tex] - [tex]\left[\begin{array}{ccc}-1&0\\5&2\\4&9\end{array}\right][/tex]
Subtract corresponding elements to obtain difference, that is
[tex]\left[\begin{array}{ccc}3+1&2-0\\-4+5&6-2\\7-4&5-9\end{array}\right][/tex]
= [tex]\left[\begin{array}{ccc}4&2\\1&4\\3&-4\end{array}\right][/tex] → B
use long division to find the quotient below (5x^5+90x^2-135x)(x+3)
Answer:
quotient: 5x^4 -15x^3 +45x^2
Step-by-step explanation:
The division is performed in the attachment. At each stage, the quotient is the ratio of the highest-degree terms in dividend and divisor.
To find the dividend for the next step, subtract the product of quotient term and divisor from the current dividend. This is essentially the same way you do long division using integers.
Find the sum of the sequence: 108, 105, 102,...,15
Answer:
1968
Step-by-step explanation:
The given sequence is a finite arithmetic sequence.
Step 1: Determine the number of terms in the sequence
For an arithmetic sequence, the nth term:
A(n)=a+(n-1)d
In the sequence:
First term, a=108Last term, l=15Common difference, d=105-108= -3Therefore, to find which term the number 15 is, we have:
15=108+(n-1)(-3)
15=108-3n+3
15=111-3n
3n=111-15
3n=96
Number of terms in the sequence, n=32
Step 2: Find the sum of the sequence
For an arithmetic sequence with a given first and last term:
[tex]Sum, S(n)=\frac{n}{2}(a+l)\\ =\frac{32}{2}(108+15)\\=16*123\\$Sum of the sequence, S(n)=1968[/tex]
Jon won 30 marbles playing horseshoes at a game night. Later, he gave 3 to each of his friends. He only has 9 left. How many friends does she have?
y+y+c-10+x If x=7, y=10 and c=8
Answer:
it is 25
Step-by-step explanation:
FIRSTLY YOU SUBSTITUTE
10+10+8-10+7
=25
Answer:
10 + 10 + 8 - 10 + 7
= 25
Step-by-step explanation:
If k(x) = 5x-6, which expression is equivalent to (k+k) (4)?
Answer:
5(4) - 6 + 5(4) - 6
Step-by-step explanation:
k(x) = 5x - 6
(k+k)(x) = 5x - 6 + 5x - 6
(k+k)(4) = 5(4) - 6 + 5(4) - 6
=> Option D is correct
Hope this helps!
The expression is equivalent to (k+k) (4) will be 5(4) - 6 + 5(4) - 6. The correct option is B.
What is an expression?Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication, and division.
Numbers (constants), variables, operations, functions, brackets, punctuation, and grouping can all be represented by mathematical symbols, which can also be used to indicate the logical syntax's order of operations and other features.
The expression will be solved as below:-
k(x) = 5x - 6
(k+k)(x) = 5x - 6 + 5x - 6
(k+k)(4) = 5(4) - 6 + 5(4) - 6
Therefore, the expression is equivalent to (k+k) (4) will be 5(4) - 6 + 5(4) - 6. The correct option is B.
To know more about Expression follow
https://brainly.com/question/723406
#SPJ6
do prisms need to have rectangular or triangular bases?
Answer: Boths
Step-by-step explanation: